Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins